Polyhydroxyalkanoate‐Modified Bacterium Regulates Biomass Structure and Promotes Synthesis of Carbon Materials for High‐Performance Supercapacitors. Issue 8 (26th March 2019) - Zhang, Kejing; Liu, Mingren; Si, Mengying; Wang, Zhongren; Zhuo, Shengnan; Chai, Liyuan; Shi, Yan
Abstract: Biomass‐derived carbons have been extensively explored as electrode materials in supercapacitors. However, the type of biomass selected and its specific structure affects the synthesis of the advanced biomass‐derived carbon materials. A green and facile method for the synthesis of carbon material with nanoscale and microscale porous structures for supercapacitors has been developed, based on regulating the original cell structure of the bacterial strain. The cell structure is modified in situ by regulating the accumulation of polyhydroxyalkanoate under controlled cultivation conditions. The novel bacterial in situ modification and nitrogen doping endow this hierarchically derived carbon material with improved performance. This material exhibits an extremely high specific capacitance (420 F g −1 at 1 A g −1 ) and long cycling stability (97 % capacitance retention after 10 000 cycles at 5 A g −1 ) in aqueous electrolytes. More importantly, the symmetric supercapacitor delivers a superior energy density of 60.76 Wh kg −1 at 625 W kg −1 in an ionic liquid electrolyte system. Moreover, all components in the synthesis are low in cost, environmentally friendly, and biocompatible. With these unique features, the bacterial self‐modification mode opens new avenues into the design and production of a wide range of hierarchical structures. Abstract : Back to life, bacteriality : The type of biomass and its specific structure affects the synthesis of advanced biomass‐derived carbon materials. A green, facile and universal method was developed for the synthesis of carbon material with nanoscale and microscale porous structures for high‐performance supercapacitor based on regulating the original cell structure of a bacterial strain.